Analysis of size and temperature effects in the ductile to brittle transition region of ferritic steels - Berejnoi, Carlos (2015)
This paper presents an analysis of ferritic steels in the ductile-to-brittle transition region that includes the determination of the temperature reference of the Master Curve, which assumes a Weibull distribution with fixed threshold and shape parameters for compact specimens of one inch thickness. Some differences arise between the scale parameter and the median of the distribution calculated from these specimens and those converted from other sizes. The dependence with size and temperature of the parameters of a non-fixed three parameter Weibull distribution were also analyzed. The estimated threshold and shape parameters resulted clearly temperature dependent, and different from those stated in the Master Curve.